1975
DOI: 10.1126/science.1114314
|View full text |Cite
|
Sign up to set email alerts
|

Myogenic Defect in Acetylcholinesterase Regulation in Muscular Dystrophy of the Chicken

Abstract: To determine whether inherited muscular dystrophy of the chicken is neurogenic or myogenic in origin, limb buds from homozygous normal and dystrophic chick embryos were exchanged prior to muscle differentiation and innervation. Biceps muscles of hatched chicks, in which muscle of the donor was innervated by nerves of the host, were analyzed for embryonic properties of muscle acetylcholinesterase and for fiber diameter, two distinctive markers for expression of the dystrophic gene. The results indicate that mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1975
1975
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Although there is no evidence in human myotubes, an altered assembly of the tetrameric forms of the enzyme has been reported during development in dys trophic mice (Poiana et at. 1985), and altered activity has also been observed in chicken dystrophy (Linkhart et al 1975). It is known that in reduced during the process of culturing, but the activity of the surface AChoE is still present (Glavinovic et al 1987).…”
Section: Discussionmentioning
confidence: 96%
“…Although there is no evidence in human myotubes, an altered assembly of the tetrameric forms of the enzyme has been reported during development in dys trophic mice (Poiana et at. 1985), and altered activity has also been observed in chicken dystrophy (Linkhart et al 1975). It is known that in reduced during the process of culturing, but the activity of the surface AChoE is still present (Glavinovic et al 1987).…”
Section: Discussionmentioning
confidence: 96%
“…On the basis of this finding the increased ACh sensitivity in DMD myotubes could be explained by the alteration of a membrane protein such as acetylcholinesterase, which has been reported in an altered assembly of tetrameric forms in dystrophic mice [24], and in dystrophic chickens. [16]. [7] DELAPORTE C., DEHAUPAS M., FARDEAU M.:…”
Section: Discussionmentioning
confidence: 99%
“…If dystrophic features can be irreversibly induced at a very early stage in cells that will give rise to muscles, experiments done after this critical period would support a primary myogenic origin of muscular dystrophy, and would not reveal the influence of the nervous system. This could explain why limb bud transplants between normal and dystrophic chicken embryos retained the characteristics of the donor animals (21). These experiments were done 36 to 48 hours later than the neural tube transplants reported here and after the critical time during which the neural tube exerts its inductive influence (10,24).…”
mentioning
confidence: 80%
“…If limb buds or muscles are transplanted between normal and dystrophic chickens, the nervous system appears to have no influence on the subsequent development of the muscle pathology (21). However, these transplant studies were not done as early in development as the neural tube transplants reported here.…”
mentioning
confidence: 93%